Generation of interspecies limited chimeric nephrons using a conditional nephron progenitor cell replacement system. Issue 1 (December 2017) - Yamanaka, S.; Tajiri, S.; Fujimoto, T.; Matsumoto, K.; Fukunaga, S.; Kim, B.; Okano, H.; Yokoo, T.
Abstract Animal fetuses and embryos may have applications in the generation of human organs. Progenitor cells may be an appropriate cell source for regenerative organs because of their safety and availability. However, regenerative organs derived from exogenous lineage progenitors in developing animal fetuses have not yet been obtained. Here, we established a combination system through which donor cells could be precisely injected into the nephrogenic zone and native nephron progenitor cells (NPCs) could be eliminated in a time- and tissue-specific manner. We successfully achieved removal of Six2+ NPCs within the nephrogenic niche and complete replacement of transplanted NPCs with donor cells. These NPCs developed into mature glomeruli and renal tubules, and blood flow was observed following transplantation in vivo. Furthermore, this artificial nephron could be obtained using NPCs from different species. Thus, this technique enables in vivo differentiation from progenitor cells into nephrons, providing insights into nephrogenesis and organ regeneration. The transplantation of tissue-specific progenitor cells may be an approach in organ regeneration. Here the authors show that the nephron progenitor population of a developing mouse kidney, when ablated, can be replaced by exogenously supplied rat nephron progenitors, generating interspecies nephrons.